Retracted: Prevalence of refractive errors and corneal topographic changes in unilateral congenital ptosis vs the fellow eye: a clinical study - Vichare, Nitin V. (International Journal of Research in Medical Sciences, 2019)
The article titled, "Prevalence of refractive errors and corneal topographic changes in unilateral congenital ptosis vs the fellow eye: a clinical study", published in the International Journal of Research in Medical Sciences, Volume 7, Issue 2, 2019, Pages 442-446, DOI: http://dx.doi.org/10.18203/2320-6012.ijrms20190350 is being retracted due to authorship dispute.